Perpendicular growth of few-layered MoS2 nanosheets on MoO3 nanowires fabricated by direct anion exchange reactions for high-performance lithium-ion batteries. Issue 45 (7th November 2016) - Liu, Hui; Chen, Xianjin; Deng, Lu; Ding, Meng; Li, Junqi; He, Xuanmeng
Abstract : The morphologies and structures can be controlled by adjusting the solvent and sulfur source although an organic–inorganic precursor was not used. Abstract : One dimensional (1D) hierarchical core–shell structures (MoO3 @MoS2 ) constructed by perpendicular growth of few-layered MoS2 nanosheets on MoO3 nanowires were successfully fabricated by a direct anion-exchange reaction of the inorganic MoO3 nanowire precursor. The morphology and structure of the products can be controlled by adjusting the hybrid solvent in the anion-exchange process, and the contents of MoS2 and MoO3 in the core–shell nanowires can be easily tuned by adding a varied amount of thiourea. Although the organic–inorganic precursor was not used, the 1D structure of the inorganic MoO3 nanowire was still maintained. An amazing feature of the MoO3 @MoS2 nanowire was its 1D hierarchical core–shell structure integrated with two-dimensional (2D) ultrathin MoS2 nanosheets and 1D MoO3 nanowires. The numerous few-layered MoS2 nanosheets grew perpendicularly on the MoO3 nanowires, providing plenty of diffusion channels for Li + during the insertion/extraction process. Due to the abundant hardly stacked MoS2 nanosheets and the synergistic effects between MoO3 nanowires and MoS2 nanosheets, this unique MoO3 @MoS2 nanowire showed greatly improved Li + storage properties when evaluated as an anode material for lithium ion batteries (LIBs).